2019
DOI: 10.1002/ese3.406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injection strategies on low‐speed marine engines using the dual fuel of high‐pressure direct‐injection natural gas and diesel

Abstract: Pilot‐ignited high‐pressure direct‐injection (HPDI) natural gas engines have drawn much attention since being proposed, as these engines can maintain high performance and lead to clean combustion compared with conventional diesel engines. This prospective concept is not only used in vehicle engines but also used in large‐scale marine engines. In this study, the effects of injection strategies of dual fuels on combustion characteristics and emissions were investigated using the computational fluid dynamics (CFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Goldsworthy [142] investigated the thermal efficiency and exhaust emissions of a heavy duty common rail marine diesel engine with ethanol-water mixtures and found that NOx emission decreased significantly with pre-injection and main injection of diesel and the injection into the intake air of 93% ethanol/water mixture. Liu et al [143] investigated effects of injection strategies on low-speed marine engines with the dual fuel of natural gas and diesel. It was found that the appropriate pilot fuel injection timing and gas injection timing simultaneously reduced NOx, HC, CO and soot.…”
Section: High Pressure Common Rail Fuel Injectionmentioning
confidence: 99%
“…Goldsworthy [142] investigated the thermal efficiency and exhaust emissions of a heavy duty common rail marine diesel engine with ethanol-water mixtures and found that NOx emission decreased significantly with pre-injection and main injection of diesel and the injection into the intake air of 93% ethanol/water mixture. Liu et al [143] investigated effects of injection strategies on low-speed marine engines with the dual fuel of natural gas and diesel. It was found that the appropriate pilot fuel injection timing and gas injection timing simultaneously reduced NOx, HC, CO and soot.…”
Section: High Pressure Common Rail Fuel Injectionmentioning
confidence: 99%
“…The DF mechanisms which were developed by Rahimi, et al [60] were obtained by merging n-heptane mechanisms and methane mechanisms. This combustion mechanism was widely used in the combustion of DF engines and made it possible to calculate cylinder pressure and NO X emissions more accurately [28,29,61]. The selected mathematical models and chemical mechanisms are listed in Table 4.…”
Section: S X U Tmentioning
confidence: 99%
“…Due to the large-bore and stroke of the engine, the small grid size causes the long calculation time. In this paper, the 20 mm base value grid was chosen to simulate the combustion process with the adaptive mesh refinement and fixed embedding grid control strategy [28,63]. The peak firing pressure and emissions products were tested and used to validate the accuracy of the model.…”
Section: S X U Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of natural gas engines have been summarized in the literature [7]. There are primarily three kinds of operating modes for natural gas engines, which are pure natural gas engines, low-pressure dual-fuel engines, and highpressure direct-injection dual-fuel engines.…”
Section: Introductionmentioning
confidence: 99%